Assessing the Burden of Kidney Disease among Type 2 Diabetic Subjects Attending a Semi-Urban Tertiary Health Facility in South-West Nigeria - Ikem, R T; Lawal-Bello, A T; Soyoye, D O; Fasanu, A N; Kolawole, B A (West African journal of medicine, 2023)
Diabetes Mellitus (DM) remains an important public health issue and its complications are important causes of morbidity and mortality. Diabetic nephropathy (DN) is one of these complications and could be prevented/delayed by early detection. This study determined the burden of DN among patients with type 2 diabetes (T2DM). This cross-sectional, hospital-based study was conducted among 100 T2DM patients attending the medical outpatient clinics of a tertiary hospital in Nigeria and 100 age- and sex-matched healthy controls. The procedure included collection of sociodemographic parameters, urine for microalbuminuria and blood samples for estimation of fasting plasma glucose, glycated haemoglobin (HbA1c), and creatinine. Estimated creatinine clearance (eGFR) was derived from two formulae - Cockroft Gault formula, and Modification of Diet in Renal Disease study (MDRD) for staging chronic kidney disease. Data were analysed using the IBM SPSS version 23 software. Participants' ages ranged from 28 years to 73 years [mean 53.0 (±10.7) years] with males accounting for 56% of the population and females 44%. Mean HbA1c was 7.6 (±1.8) % among the subjects; 59% had poor glycaemic control with HbA1c >7% (p-value <0.001). Overt proteinuria was present in 13% of T2DM participants while 48% had microalbuminuria compared to the non-diabetic group where 2% had overt proteinuria and 17% had microalbuminuria. Using the eGFR, chronic kidney disease was present in 14% of T2DM group and in 6% of the non-diabetic population. Increased age [OR= 1.09; 95%CI (1.03-1.14)], male sex [OR = 3.50; 95%CI (1.13 10.88)], and duration of diabetes [OR =1.01; 95%CI (1.00-1.01)] were associated with DN. The burden of diabetic nephropathy is high in the T2DM patients attending our clinic and this is linked with advancing age.